Optimization Axial T2WI Lumbar MRI in Spinal Stenosis: Effects of GRAPPA Acceleration Factor on Image Quality and Anatomy - Diah Nisaa Harumsari; Dwi Rochmayanti; Nanang Sulaksono (RSUP Dr. Kariadi, 2025)
BACKGROUND: Patients with lumbar spinal stenosis (LSS) who struggle to lie down for long periods may encounter issues during lumbar MRI exams. GRAPPA, a parallel imaging method to speed up MRI scans, can reduce the Signal to Noise Ratio (SNR), affecting image quality and anatomical information. AIMS: This study aims to find the best GRAPPA acceleration factor by assessing its effect on image quality and anatomical information. METHOD: This study involved scans on 10 Lumbar MRI patients with LSS cases. The scans were performed using a Siemens Magnetom Aera 1.5 Tesla MRI machine with T2WI TSE axial cut. Each patient underwent 4 treatments with acceleration factors of 1 (without GRAPPA acceleration factor), 2, 3, and 4. Image quality was analysed using ROI to obtain SNR and CNR values. The radiologist assessed the anatomical information on the images. The analysis included a one-way ANOVA and the Kruskal-Wallis test was performed for image quality and anatomical information. RESULT: The research found that the GRAPPA acceleration factor significantly affects image quality and anatomical information in axial T2WI TSE Lumbar MRI scans for patients with LSS (p-value < 0.01). A factor of 3 reduces examination time by 65.35% without significant differences (p > 0.05) in image quality and anatomical information. CONCLUSION: The acceleration factor in axial T2WI TSE lumbar MRI significantly affects image quality and anatomical information for lumbar spinal stenosis cases. An acceleration factor of 3 is optimal for maintaining quality and anatomical information.